PERBEDAAN RATA-RATA TEKANAN DARAH PADA PERAWAT DENGAN KERJA SHIFT PAGI, SIANG DAN MALAM DI RUANG RAWAT INAP RUMAH SAKIT PKU MUHAMMADIYAH GOMBONG - Mukhliz Fauzi; Han doyo; Madkhan Anis (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2009)
Blood pressure is remaining problem for people who have overload activity during work time. This situation is not only happened for people who have work time in the night and afternoon, but also in the morning shift duty. Base on the result of the preliminary interview with the nurses in PKU Muhammadiyah Gombong general hospital, they declare that the have experience of work hard in the evening shift and they have disturbance of sleeping time after night.It can be concluded that it will make the disturbance of human physiology, so that it will influence of human blood pressure. The aim of this study is to show the blood pressure differences of nurses who work in the morning, afternoon and night shift duty at the PKU Muhammadiyah Gombong general hospital This research was applying descriptive analysis by non-randomized control group pretest posttest design. The population of the study consists of 75 nurses who work medical and surgical ward at PKU Muhannadiyah Gombong general hospital. Purposive sampling method was used to take sample. Of 37 nurses were involved in this study. The data were taken from the sample by measuring blood pressure in each work shift before and after working and the analysis was used paired t-test and Analysis of Varian (ANOVA). The result shows that there were significant differences of blood pressure after and before morning, afternoon and night shift duty at p 0.000 by paired t test analysis, meanwhile there were also significant differences of blood pressure during morning, afternoon and night shift duty at p=0.000. There are significant differences of blood pressure after and before morning, afternoon and night shift duty. Meanwhile there are also significant differences of blood pressure during morning, afternoon and night shift duty Keywords: Blood Pressure nurses, Morning Shift, Afternoon Shift And Night Shift duty